2002
DOI: 10.3354/meps225045
|View full text |Cite
|
Sign up to set email alerts
|

Mega-epibenthic diversity: a polar comparison

Abstract: The diversity of Arctic (off northeast Greenland) and Antarctic (Weddell and Bellingshausen Seas) megabenthic assemblages was compared using underwater video at depths between 30 and 550 m. The number of taxa found at each station was highest on the Weddell Sea shelf, which can be interpreted as being a result of the long isolation of the Antarctic fauna. However, the withinhabitat (α) diversity of the Weddell Sea assemblages did not differ significantly from those off Greenland or in the Bellingshausen Sea in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Conversely, species diversity should be lower upstream, on the western side of the Antarctic Peninsula, and that is exactly the pattern Raguá- Gil et al (2004) found in their analysis of three shallow-water communities. Similar differences in species richness between the eastern Weddell Sea and the western coast of the Antarctic Peninsula were reported by Starmans and Gutt (2002). On a different scale, Linse et al (2006) likewise found the highest diversity of molluscs to be in the Weddell Sea, east of the Scotia Arc, and the lowest on the western side of the Antarctic Peninsula (although this might have been due to sampling discrepancies).…”
Section: Isolation and Speciation Via The Antarctic Circumpolar Curresupporting
confidence: 54%
“…Conversely, species diversity should be lower upstream, on the western side of the Antarctic Peninsula, and that is exactly the pattern Raguá- Gil et al (2004) found in their analysis of three shallow-water communities. Similar differences in species richness between the eastern Weddell Sea and the western coast of the Antarctic Peninsula were reported by Starmans and Gutt (2002). On a different scale, Linse et al (2006) likewise found the highest diversity of molluscs to be in the Weddell Sea, east of the Scotia Arc, and the lowest on the western side of the Antarctic Peninsula (although this might have been due to sampling discrepancies).…”
Section: Isolation and Speciation Via The Antarctic Circumpolar Curresupporting
confidence: 54%
“…Nevertheless, these totals can provide only a very superficial knowledge about differences and similarities between those two polar regions, and diversity may further vary depending on the taxonomic or ecological group. So far, there have only been few attempts to compare benthic diversity on Arctic and Antarctic shelves, and those included only large scale syntheses comparing either the Arctic and Antarctic as a whole (Knox & Lowry, 1977), or large basins, like the Laptev Sea and Weddell Sea (Piepenburg et al, 1997;Starmans et al, 1999;Starmans & Gutt, 2002;Sirenko, 2009). Moreover, those analyses were mostly focused on mega-epibenthic fauna, not always collected with quantitative sampling gear.…”
Section: Introductionmentioning
confidence: 99%
“…An average similarity of 84.2 % was found between images in 2002, along with 81.2 % average similarity between images in 2007, and 88.2 % average similarity between images in 2012. In 2002, the largest percent contribution to within-year similarity was made by the brittle star O. gracilis (2002: 96.4 %, 2007: 94.8 %, 2012: 71.3 %). In 2012, other species also contributed to the within-year similarity, and these included cf.…”
Section: Differences Between Yearsmentioning
confidence: 99%
“…In recent years, towed-camera studies have been undertaken in the Arctic at stations in the central Arctic (Gamber and Clark, 1978), Canadian Basin (MacDonald et al, 2010;Afanasév, 1978), north Alaska (Bluhm et al, 2005), Makarov Basin (Hunkins et al, 1960), the Alpha Ridge (Paul and Menzies, 1974), in the Greenland Sea (Jones et al, 2007;Mayer and Piepenburg, 1996;Schulz et al, 2010;Starmans and Gutt, 2002), in the Fram Strait (Bergmann et al, 2011b;Soltwedel et al, 2009) and Svalbard waters (Piepenburg et al, 1996a;Bergmann et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%